The relative pricing of sovereign credit risk after the Eurozone crisis. (April 2021) - Corvino, Raffaele; Ruggiero, Francesco
Abstract: We investigate whether riskier European countries compensate their debtholders properly by paying sufficiently higher bond yields than those of safer European countries, during and after the sovereign debt crisis of 2010–2012. Using the relative pricing between credit default swap (CDS) spreads and bond yields, we show that an inconsistent cross-sectional relationship between sovereign default risk and sovereign bond yields emerges during the crisis period for all European countries. However, after the announcement of the Outright Monetary Transaction (OMT) program by the European Central Bank, the consistent cross-sectional relationship between default risk and bond yields is restored for the Eurozone countries only, a result likely due to a reduction in transaction costs.